Identities at Work - Brown, Alan; Kirpal, Simone R.; Rauner, Felix (Technical and Vocational Education and Training: Issues, Concerns and Prospects, 2007)
This edited volume on Identities at Work brings together international theory and empirical research that deals with continuity and change of identity formation processes at work under conditions of modern working processes and labour market flexibility. Modern work processes in manufacturing and service organisations increasingly rely upon responsible and competent employees who are willing and able to engage in the tasks that their job requires and in continuous learning. That employees are able to engage in taking up new forms of responsibility and master complex work situations is, on the one hand, dependent upon employees' skills and how well they are trained. On the other hand, it requires that employees identify with what they do and commit to their work and the performance of tasks. By bringing together perspectives from sociology, psychology, organisational management and vocational education and training the contributions in this volume connect the debates of skills formation, human resources development and careers with individual's work commitment and professional orientations in various ways. With this focus the volume presents a new research perspective based on an interdisciplinary and international approach. We argue that in times of globalisation and rapidly changing work realities such an approach is needed to better understand and analyse what is required to equip and prepare the workforce to meet international labour market demands. In this sense the publication shall serve as a useful resource to researchers and policy makers working in the fields of skills formation, human resources development and organisational management.